PENINGKATAN PRESTASI BELAJAR MATEMATIKA PADA MATERI STATISTIKA DENGAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) - Sugiyanta Sugiyanta (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2017)
This research aims to improve learning achievement in Mathematics on the subject of Opportunities using Team Assisted Individualization (TAI) learning model at the grade IX-E of SMP 3 Imogiri academic year 2016/2017. This type of research is a classroom action research conducted in three cycles, in which each cycle consists of the stages of planning, implementation, observation and reflection. The subjects of this research were the students of grade IX-Eof SMP Imogiri 3 academic year 2016/2017, meanwhile the object was the students’ achievement in learning Mathematics. The results showed that the useof Team Assisted Individualization (TAI) learning model can increase students’ achievement on the grade IX-E of SMP 3 Imogiri with the results of each cycle showed as follows: Students who already met the KKM (Kriteria Ketuntasan Minimal) on the cycle 1 was 87,50% and the cycle 2 was 100%. The average value was 82,50 on the cycle 1, and 95,00 . The value range between the highest and lowest score was 80,00 on the cycle 1, 20,00 on the cycle 2.